EVALUATION OF MAJOR SYMPTOMS IN THE EARLY DETECTION OF BURNOUT SYNDROME IN TEACHERS (CIPEEX, 2022)
BURNOUT SYNDROME (SB) IS A PSYCHOSOCIAL EVENT THAT ARISES AS A RESPONSE TO CHRONIC STRESSORS AT WORK, ESPECIALLY THE EMOTIONAL TENSION CAUSED BY OVER-DEALING WITH PEOPLE. IT PREDOMINANTLY AFFECTS MIDDLE AND HIGH SCHOOL TEACHERS, DUE TO THEIR GREATER EXPOSURE TO CONFLICTING ENVIRONMENTS AND HIGH LABOR DEMAND. CURRENTLY, THE PRIMARY PROPHYLACTIC METHOD IS THE EARLY DETECTION OF SYMPTOMS OF THE SYNDROME AND TREATMENT OF THESE. THEREFORE, THIS STUDY AIMS TO ADDRESS THE MAIN SYMPTOMS IN THE EARLY DETECTION OF SB IN TEACHERS. THE METHODOLOGY USED WAS RESEARCH IN ELECTRONIC SITES AND SCIENTIFIC RESEARCH PLATFORMS SUCH AS PUBMED, SCIELO AND GOOGLE SCHOLAR, USING THE DESCRIPTORS "BURNOUT SYNDROME", "SIGNS AND SYMPTOMS", "DIAGNOSIS" AND "TEACHERS". THE RESEARCH WAS CONDUCTED AMONG ARTICLES PUBLISHED IN THE PERIOD BETWEEN 2014 TO 2018. DUE TO THE SIMILARITY OF SYMPTOMS, BURNOUT WAS CONFUSED FOR MANY YEARS WITH OTHER MENTAL DISORDERS, SUCH AS DEPRESSION AND EXCESSIVE STRESS. TODAY, ALTHOUGH THIS SYNDROME IS ALREADY RECOGNIZED IN ICD-10 AND INCLUDED IN THE NEW LIST OF OCCUPATIONAL AND RELATED DISEASES (MINISTRY OF HEALTH, 1999), ITS SIZE AND SPECIFIC CHARACTERIZATION ARE LITTLE KNOWN. IN THIS CONTEXT, IT IS CONCLUDED THAT IT IS EVIDENT THE IMPORTANCE OF PREVIOUSLY IDENTIFYING THE FIRST MANIFESTATIONS THAT APPEAR IN THE SB, SO THAT IT IS USED AS A WARNING SIGNAL TO PROFESSIONALS ABOUT THE RISK FACTORS THAT MAKE THEM SUSCEPTIBLE TO THIS PATHOLOGY. AFTER ALL, THE EARLIER THE DISEASE IS IDENTIFIED, THE GREATER THE CHANCES OF MITIGATING THE POSSIBLE CONSEQUENCES OF THIS DISEASE.
Keywords: Burnout Syndrome. Signals and symptons. Diagnosis. Teachers.